2016
DOI: 10.1038/aps.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the KCNQ1 gene are associated with the therapeutic responses of sulfonylureas in Chinese patients with type 2 diabetes

Abstract: KCNQ1 channel is a member of the voltage-gated potassium channel KQT-like subfamily. The KCNQ1 gene has recently been identified as a susceptibility locus for type 2 diabetes mellitus (T2DM). In the present study, we examined the effects of KCNQ1 variants on the therapeutic response to modified-release gliclazide (gliclazide MR) treatment in Chinese patients newly diagnosed with T2DM. A total of 100 newly diagnosed T2DM patients without a history of any anti-diabetic medications were treated with gliclazide MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 49 publications
0
6
0
2
Order By: Relevance
“…∆FPG was significantly higher in TT+TG group than in GG group (P=0.016). Li et al [14] expounded the association between rs2237892/rs2237895 and modified-release gliclazide effect in Chinese T2DM patients. In rs2237892 variant, carriers of TT genotype exhibited higher 2-h glucose levels after 16 weeks of sulfonylureas gliclazide MR (modified-release gliclazide) treatment (P=0.044).…”
Section: Pharmacogenomics and Pharmacokinetics/ Pharmacodynamics Of Sulfonylureasmentioning
confidence: 99%
“…∆FPG was significantly higher in TT+TG group than in GG group (P=0.016). Li et al [14] expounded the association between rs2237892/rs2237895 and modified-release gliclazide effect in Chinese T2DM patients. In rs2237892 variant, carriers of TT genotype exhibited higher 2-h glucose levels after 16 weeks of sulfonylureas gliclazide MR (modified-release gliclazide) treatment (P=0.044).…”
Section: Pharmacogenomics and Pharmacokinetics/ Pharmacodynamics Of Sulfonylureasmentioning
confidence: 99%
“…The KCNQ1 rs163184 variant was found to markedly reduce FPG in patients with diabetes on sulfonylurea treatment [ 58 ]. Two studies from China revealed that KCNQ1 polymorphisms are associated with response to sulfonylurea therapy in patients with newly diagnosed T2D [ 59 , 60 ].…”
Section: Pharmacogenomics For Diabetes Mellitusmentioning
confidence: 99%
“…A large number of genetic polymorphisms affect the response to oral anti-diabetic drugs. Genes encoding SLC2A2 and organic cation transporters (OCT1, OCT2, and OCT3) are associated with glycemic response to metformin [17][18][19], while SLCO1B3 and KCNQ are associated with sulfonylureas response [20,21]. However, these genes have little applicability in therapy due to the different polymorphisms among different populations.…”
Section: Potential Targets For T2dm Gene Therapymentioning
confidence: 99%